Adult Growth Hormone Deficiency: Current Concepts - FUKUDA, Izumi (Neurol Med Chir (Tokyo), 2014)
The clinical syndrome of adult growth hormone deficiency (AGHD) was widely recognized in the 1980s. In this review, we first describe the clinical features and diagnosis of AGHD and then state the effects of growth hormone (GH) therapy for these patients. The main characteristics of AGHD are abnormal body composition, dyslipidemia, insulin resistance, and an impaired quality of life (QoL) due to decreased psychological well-being. For diagnosing AGHD, the international consensus guidelines have suggested that an insulin tolerance test (ITT) is the gold standard, but in Japan, the growth hormone releasing peptide-2 (GHRP-2) test is available and is recommended as a convenient and safe GH stimulating test. The cut-off for diagnosing severe AGHD is a peak GH concentration of 9 g/L during the GHRP-2 test. Since 2006, GH therapy has been approved for Japanese patients with severe AGHD. For adults, GH replacement therapy should be initiated at a low dose (3 g/kg body weight/day), followed by individualized dose titration while monitoring patients' clinical status and serum insulin-like growth factor-I (IGF-I) concentrations. A variety of favorable effects of GH replacement have been indicated; however, it has not yet been established fully whether there is a direct effect of GH treatment on reducing mortality.